Development of a K(+)-channel probe and its use for identification of an intracellular plant membrane K+ channel. - Mi, F (1995)
Polyclonal antibodies were generated against a 9-amino acid, synthetic peptide corresponding to the selectivity filter in the pore region of K(+)-channel proteins. The sequence of amino acids in the ion-conducting pore region of K+ channels is the only highly conserved region of members of this protein family. The objectives of the present work were (i) to determine whether the anti-channel pore peptide antibody was immunoreactive with known K(+)-channel proteins and (ii) to demonstrate the usefulness of the antibody by employing it to identify a newly discovered K(+)-channel protein. Anti-channel pore peptide was immunoreactive with various K(+)-channel subtypes native to a number of different species. Immunoblot analysis demonstrated affinity of the antibody for the drk1, maxi-K, and KAT1 K(+)-channel proteins. Studies also suggested that the anti-channel pore peptide antibody did not immunoreact with membrane proteins other than K+ channels. The anti-channel pore peptide antibody was used to establish the identity of a 62-kDa chloroplast inner envelope polypeptide as a putative component of a K(+)-channel protein. It was concluded that an antibody generated against the conserved pore region/selectivity filter of K+ channels has broad but selective affinity for this class of proteins. This K(+)-channel probe may be a useful tool for identification of K(+)-channel proteins in native membranes.